Misleading Promotion as an Unlawful Act: An Analysis of Article 1365 of the Civil Code - Agus, Azwir (Rechtsvinding, 2025)
Promotional practices are an important instrument in trade and marketing activities. However, in practice, many businesses engage in misleading promotions, which can be detrimental to consumers. Misleading promotions can include information that is incorrect, incomplete, or creates a false perception of the goods or services being offered. This paper aims to analyze misleading promotions as an unlawful act based on Article 1365 of the Civil Code (KUHPerdata). The research method used is normative legal research with a statutory and conceptual approach. The results show that misleading promotions fulfill the elements of an unlawful act, namely the existence of an act, the act is unlawful, there is an error, the occurrence of a loss, and a causal relationship between the act and the loss. Thus, businesses can be held civilly liable for losses experienced by consumers due to misleading promotions.